Multifunctional Control Strategy for Asymmetrical Cascaded H-Bridge Inverter in Microgrid Applications - Mortezaei, Ali; Simoes, Marcelo Godoy; Bubshait, Abdullah S.; Curi Busarello, Tiago Davi; Marafao, Fernando P. [UNESP]; Al-Durra, Ahmed (Ieee-inst Electrical Electronics Engineers Inc, 2017)
A multifunctional control strategy for a single-phase asymmetrical cascaded H-bridge multilevel inverter (ACHMI), suitable for microgrid systems with nonlinear loads, is presented. The primary advantage of ACHMI is to produce a staircase output voltage with low harmonic content utilizing unequal dc voltages on the individual H-bridge cells. In a grid-connected mode of operation, the control strategy of theACHMIis based on the conservative power theory, providing selective disturbing current compensation besides injecting its available energy. In autonomous mode of operation, two different control methods along with a damping resistor in the filter circuit are developed for regulation of the ACHMI instantaneous output voltage in a variety of load conditions. The first method is a single-loop voltage control scheme without the need of any current measurement. The second one is a multiloop voltage control scheme with a load current feedforward compensation strategy and preservation of the grid-connected current control scheme. The steady-state response and stability of both voltage control schemes are analyzed, and based on the application requirement, the control schemes are implemented individually. The effectiveness of each control strategy is experimentally verified using a hardware-in-the-loop setup with the control algorithm implemented in the TMSF28335 DSP microcontroller.
Keywords: Conservative power theory (CPT); distributed generation (DG); microgrid; multilevel inverter; power quality improvement